Evaluating the ability of semen cryopreservation of Blance Blue Belge bull cattle in Vietnam - Duc, Nguyen Huu; Giang, Pham Thu; Nguyen, Tran Thi Binh; Mai, Nguyen Thi; Phong, Bui Dai (Vietnam Journal of Biotechnology, 2021)
The objective of this study was to determine the semen cryopreservation capacity of BBB bulls in Hanoi-Vietnam. Research conducted on the fresh semen collected from 05 BBB bulls. Results showed that semen color was normal (milky white, ivory white, ivory yellow), semen volume ranged from 6.35 mL to 7.48 mL (P <0.05), initial motility of semen ranged from 80.53% to 82.92% (P <0.05), sperm concentration in semen  ranged from 1.02 x 109 sperms/ml to 1.12 x 109 sperms/mL (P <0.05), abnormal sperm ratio ranged from 6.45% to 8.12% (P <0.05), alive sperm ratio ranged from 76.34% to 82.97% (P <0.05), sperm motility after thawing from straw semen ranged from 71.33% to 75.92% (P<0.05). In conclusion, successfully semen collection from 05 breeding BBB bulls at Hanoi Cattle Breeding Joint Stock Company, semen samples had normal color and good quantity and quality, suitable for production of frozen semen; and semen cryopreservation of straws of the 05 bull BBB semen mentioned at -196oC, sperm motility after freezing-thawing reached the economic and technical norms of 675/2014 of the Ministry of Agriculture and Rural Development.